Polyacrylonitrile (PAN)-based carbon hollow fiber membrane for O2/N2 gas separation - Saufi, S. M.; Ismail, A. F.; Abdullah, M. S. (2004)
Polyacrylonitrile (PAN) was used as an alternative precursor for making carbon membranes for gas separation. Nitrogen gas pyrolysis system was applied in order to convert the PAN polymer membranes into PAN based carbon hollow fiber membranes. The effect of pyrolysis temperature on the separation performance of carbon membranes for gas separation was studied. The temperature range from 500-800Â°C was studied during pyrolysis process. The resultant carbon hollow fiber membranes were tested with pure oxygen and nitrogen as test gases. The highest selectivity of PAN carbon membrane for O2/N2 separation is about 1. These permeation data represents the first reported data for PAN as a precursor in literature. Such data can be a useful guide to tailor made the separation performance of PAN based carbon membrane in the future.